Evidence of π‐stacking interactions in the self‐assembly of hIAPP22‐29. Issue 4 (15th January 2013) - Profit, Adam A.; Felsen, Valentina; Chinwong, Justina; Mojica, Elmer‐Rico E.; Desamero, Ruel Z. B.
Abstract The role aromatic amino acids play in the formation of amyloid is a subject of controversy. In an effort to clarify the contribution of aromaticity to the self‐assembly of human islet amyloid polypeptide (hIAPP)22‐29, peptide analogs containing electron donating groups (EDGs) or electron withdrawing groups (EWGs) as substituents on the aromatic ring of Phe‐23 at the para position have been synthesized and characterized using turbidity measurements in conjunction with Raman and fluorescence spectroscopy. Results indicate the incorporation of EDGs on the aromatic ring of Phe‐23 virtually abolish the ability of hIAPP22‐29 to form amyloid. Peptides containing EWGs were still capable of forming aggregates. These aggregates were found to be rich in β‐sheet secondary structure. Transmission electron microscopy images of the aggregates confirm the presence of amyloid fibrils. The observed difference in amyloidogenic propensity between peptides containing EDGs and those with EWGs appears not to be based on differences in peptide hydrophobicity. Fluorescence and Raman spectroscopic investigations reveal that the environment surrounding the aromatic ring becomes more hydrophobic and ordered upon aggregation. Furthermore, Raman measurements of peptide analogs containing EWGs, conclusively demonstrate a distinct downshift in the CC ring mode (ca. 1600 cm−1) upon aggregation that has previously been shown to be indicative of π‐stacking. While previous work has demonstrated that π‐stacking is not an absolute requirement for fibrillization, our findings indicate that Phe‐23 also contributes to fibril formation through π‐stacking interactions and that it is not only the hydrophobic nature of this residue that is relevant in the self‐assembly of hIAPP22‐29. © Proteins 2013. © 2012 Wiley Periodicals, Inc.